Modernisasi Kurikulum Muadalah melalui Integrasi Teknologi Digital Berbasis Deep Learning di Pesantren Salafiyah - rahma aulia; Febriyanti Febriyanti; Achmad Isa Al Firdausi (Simpati, 2025)
Modernization of education in Islamic boarding schools is an important need to maintain the relevance of learning in the digital era. Salafiyah Islamic boarding schools, which are synonymous with the traditional approach through the study of the Yellow Book, face the challenge of adapting technological developments without losing their scientific character. This research aims to develop a model of curriculum modernization through the integration of deep learning-based digital technology  to improve the effectiveness of learning and the quality of academic evaluation. The methods used include literature studies, observation of the learning process, and trial implementation of digital learning tools equipped with deep learning algorithms  for student ability analysis. The results of the study show that the application of deep learning technology  is able to speed up the competency mapping process, provide automatic feedback on reading and comprehension of classical texts, and assist teachers in monitoring the development of students more accurately. This integration also increases interest in learning and strengthens the mula curriculum system without shifting the traditional values of the Islamic boarding school. Thus, technology-based modernization can be a strategic solution to bridge the classical approach and the needs of 21st century learning in Salafi Islamic boarding schools.